Global human smuggling: buying freedom in a retreating world - Achilli, Luigi; Kyle, David (Johns Hopkins University Press, 2023)
"This book explores human smuggling in several nuanced forms across diverse regions, examining its deep historical, social, economic, and cultural roots and its broad political consequences"--